Lidocaine infusions in chronic pain management: A prospective case series analysis. Issue 3 (June 2022) - Vacher, Elizabeth; Kosela, Monika; Song-Smith, Charlie; Morell-Ducos, Fausto; Fayaz, Alan
Chronic pain conditions are prevalent and cause a significant burden of disease. Intravenous lidocaine infusions have been reported to have an analgesic effect in patients with chronic neuropathic pain, but there is limited data supporting the efficacy of lidocaine across other chronic pain phenotypes. Our study aimed to evaluate the efficacy of a single infusion of intravenous lidocaine for pain relief and the impact on quality of life. We evaluated data from 74 patients with chronic pain who were treated with intravenous lidocaine at a specialist pain centre. Participants completed a questionnaire consisting of the Brief Pain Inventory (BPI) Short Form and additional EQ-5D quality of life metrics, before treatment and at follow-up. Data comparing pain severity did not demonstrate a statistically significant change after treatment when averaged across the entire patient cohort (6.15–5.88, p = .106), irrespective of gender or pain phenotype. Scores for pain interference showed statistically significant reductions following treatment (7.05–6.41, p = .023), which may have been driven through improvements in sleep (7.41–6.35, p = .001); however, these reductions are not clinically significant. The patient cohort was stratified into responders and non-responders based on >30% improvement in response to an overall impression of pain reduction question following treatment. In the 'responder' cohort, pain intensity scores showed a statistically significant reduction post-infusion (6.18–5.49, p = .0135), but no change was apparent for non-responders (6.07–6.09, p = .920). There were no differences between responders and non-responders for pain sub-types in our study. This study found no difference in pain outcomes in a cohort of patients with chronic pain, a mean of 63 days following a single lidocaine infusion. However, a specific subgroup of responders may show slight improvements in some pain outcomes that may warrant further exploration.